A Total Evidence Phylogenetic Analysis of Pinniped Phylogeny and the Possibility of Parallel Evolution Within a Monophyletic Framework - Paterson, Ryan S.; Rybczynski, Natalia; Kohno, Naoki; Maddin, Hillary C. (Frontiers in Ecology and Evolution, 2020)
In the present study, a series of phylogenetic analyses of morphological, molecular, and combined morphological-molecular datasets were conducted to investigate the relationships of 23 extant and 44 fossil caniforme genera, in order to test the phylogenetic position of putative stem pinniped Puijila within a comprehensive evolutionary framework. With Canis as an outgroup, a Bayesian Inference analysis employing tip-dating of a combined molecular-morphological (i.e., Total Evidence) dataset recovered a topology in which musteloids are the sister group to a monophyletic pinniped clade, to the exclusion of ursids, and recovered Puijila and Potamotherium along the stem of Pinnipedia. A similar topology was recovered in a parsimony analysis of the same dataset. These results suggest the pinniped stem may be expanded to include additional fossil arctoid taxa, including Puijila, Potamotherium, and Kolponomos. The tip-dating analysis suggested a divergence time between pinnipeds and musteloids of 45.16 million years ago (Ma), though a basal split between otarioids and phocids is not estimated to occur until 26.52 Ma. These results provide further support for prolonged freshwater and nearshore phases in the evolution of pinnipeds, prior to the evolution of the extreme level of aquatic adaptation displayed by extant taxa. Ancestral character state reconstruction was used to investigate character evolution, to determine the frequency of reversals and parallelisms characterizing the three extant clades within Pinnipedia. Although the phylogenetic analyses did not directly provide any evidence of parallel evolution within the pinniped extant families, it is apparent from the inspection of previously-proposed pinniped synapomorphies, within the context of a molecular-based phylogenetic framework, that many traits shared between extant pinnipeds have arisen independently in the three clades. Notably, those traits relating to homodonty and limb-bone specialization for aquatic locomotion appear to have multiple origins within the crown group, as suggested by the retention of the plesiomorphic conditions in early-diverging fossil members of the three extant families. Thus, while the present analysis identifies a new suite of morphological synapomorphies for Pinnipedia, the frequency of reversals and other homoplasies within the clade limit their diagnostic value.